Sistem Berbasis Kasus untuk Konseling Remaja SMP dalam Menghadapi Era New Normal - Frestiany Regina Putri; Sri Kusumadewi; Hepi Wahyuningsih (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In the new normal era that has been set by the government, all educational institutions also impose face-to-face meetings or offline schools for their students. The existence of an offline school that is applied, of course, causes various events that are often experienced by children. This condition requires parents and teachers, especially Guidance Counseling (BK) teachers to be wise in making decisions, so that children do not experience behavioral disorders that will greatly affect their mental condition. This study aims to help schools and parents to make the right decisions according to the problems experienced by children. Solutions are provided through a case-based system, on the recommendation of the counselor. The research stages consist of (1) Literature Review (2) Modeling, (3) Model Evaluation, and (4) Prototype Development. This study resulted in a case-based system for junior high school youth counseling that could be used by junior high school teachers and parents, or those in need. System testing by users produces solutions for validation from counselors that are in accordance with reality, and can be used as a reference for solving problems in children in the new normal era.